Yi-Zhi-Fang-Dai Formula Exerts Neuroprotective Effects Against Pyroptosis and Blood–Brain Barrier–Glymphatic Dysfunctions to Prevent Amyloid-Beta Acute Accumulation After Cerebral Ischemia and Reperfusion in Rats - Lyu, Zhongkuan; Li, Qiyue; Yu, Zhonghai; Chan, Yuanjin; Fu, Lei; Li, Yaming; Zhang, Chunyan (Frontiers in Pharmacology, 2021)
Background: Dysfunctional blood-brain barrier (BBB)-glymphatic system is responsible for triggering intra-cerebral amyloid-beta peptide (Aβ) accumulation and acts as the key link between ischemic stroke and dementia dominated by Alzheimer's disease (AD). Recently, pyroptosis in cerebral ischemia and reperfusion (I/R) injury is demonstrated as a considerable mechanism causing BBB-glymphatic dysfunctions and Aβ acute accumulation in brain. Targeting glial pyroptosis to protect BBB-glymphatic functions after cerebral I/R could offer a new viewpoint to prevent Aβ accumulation and post-stroke dementia. Yi-Zhi-Fang-Dai Formula (YZFDF) is an herbal prescription used to cure dementia with multiple effects of regulating inflammatory responses and protecting BBB against toxic Aβ-induced damage. Hence, YZFDF potentially possesses neuroprotective effects against cerebral I/R injury and the early pathology of post-stroke dementia, which evokes our current study. Objectives: The present study was designed to confirm the potential efficacy of YZFDF against cerebral I/R injury and explore the possible mechanism associated with alleviating Aβ acute accumulation. Methods: The models of cerebral I/R injury in rats were built by the method of middle cerebral artery occlusion/reperfusion (MCAO/R). Firstly, neurological function assessment and cerebral infarct measurement were used for confirming the efficacy of YZFDF on cerebral I/R injury, and the optimal dosage (YZFDF-H) was selected to conduct the following experiments, which included Western blotting detections of pyroptosis, Aβ1-42 oligomers and NeuN, immunofluorescence observations of glial pyroptosis, aquaporin-4 (AQP-4) and Aβ locations, brain water content measurement, SMI 71 (a specific marker for BBB)/AQP-4 immunohistochemistry and Nissl staining to further evaluate BBB-glymphatic functions and neuronal damage, respectively. Results: YZFDF obviously alleviated neurological deficits and cerebral infarct after cerebral I/R in rats. Furthermore, YZFDF could inactivate pyroptosis signaling via inhibiting caspase-1/11 activation and gasdermin D cleavage, ameliorate glial pyroptosis and neuroinflammation, protect against BBB collapse and AQP-4 depolarization, prevent Aβ acute accumulation and Aβ1-42 oligomers formation, reduce neuronal damage and increase neurons survival after reperfusion. Conclusion: Our study indicated that YZFDF could exert neuroprotective effects on cerebral I/R injury and prevent Aβ acute accumulation in brain after cerebral I/R associated with inhibiting neuroinflammation related pyroptosis and BBB-glymphatic dysfunctions.